Antibacterial Effect of Human Milk against Streptococcus pyogenes: an in vitro Study - Novi Vicahyani Utami; Nurul Nadiya Binti Abdul Razak; Dzulfikar D. Lukmanul Hakim (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Streptococcus pyogenes infection is one of the common upper respiratory infections among children. Human milk has antibacterial properties that may play a role against infections. The study was conducted to observe the antibacterial effect of human milk against Streptococcus pyogenes.Methods: This was an in vitro experimental study conducted on October–November 2012 in Microbiology Laboratory, Faculty of Medicine, Universitas Padjadjaran, Bandung, using agar well diffusion method. Human milk was collected from eligible donors and tested at concentrations of 70%, 80%, 90%, and 100% dilution with water. Inhibition zone formed surrounding the wells were measured after 24 hours of incubation.Results: All samples incubated with human mils (in concentration of 70%, 80%, 90% and 100%) inhibited the growth of Streptococcus pyogenes, with the inhibition zone mean diameters of 26.33, 28.00, 28.00 and 28.33mm, respectively, compared to the well containing sterile aquadest that did not show any zone of inhibition.Conclusions: Human milk has an in vitro antibacterial effect against Streptococcus pyogenes. Giving human milk to babies is important for preventing infectious diseases.